Development of environmental auditing - Tovma, N. (Journal of Economic Research & Business Administration, 2015)
This article sets out the methodology of environmental auditing. Are views of environmental auditing. Describes the special tests and measurements in order to validate the reporting on the impact on the environment; conformity assessment production process environmental requirements; conformity assessment system of industrial monitoring and control environmental requirements; assess the level of staff training. Environmental auditing refers to the auditing of organizations social and environmental reporting requirements and reporting thereon going beyond financial statements auditing. In this case auditors are providing assurance services to the organizations social and environmental activities. Customers, communities, and governments around the world are actively expressing concern on climate change and environmental degradation. Consequently, organizations under pressure to reduce any harmful effects on the environment.